Structural characterization of a new dextran with a low degree of branching produced by Leuconostoc mesenteroides FT045B dextransucrase - Vettori, Mary Helen Palmuti Braga [UNESP]; Franchetti, Sandra Mara Martins [UNESP]; Contiero, Jonas [UNESP] (Elsevier, 2012)
This paper offers the physical and chemical characterization of a new dextran produced by Leuconostoc mesenteroides FT045B. The chemical structure was determined by Fourier Transform Infrared spectroscopy and 1H Nuclear Magnetic Resonance spectroscopy. The dextran was hydrolyzed by endodextranase; the products were analyzed using thin layer chromatography and compared with those of commercial B-512F dextran. The number-average molecular weight and degree of polymerization of the FT045B dextran were determined by the measurement of the reducing value using the copper bicinchoninate method and the measurement of total carbohydrate using the phenol-sulfuric acid method. The data revealed that the structure of the dextran synthesized by FT045B dextran sucrase is composed of d-glucose residues, containing 97.9% α-(1,6) linkages in the main chains and 2.1% α-(1,3) branch linkages compared with the commercial B-512F dextran, which has 95% α-(1,6) linkages in the main chains and 5% α-(1,3) branch linkages. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Comparison with commercial B-512F dextran; Dextran; Leuconostoc mesenteroides FT045B dextransucrase; Structural characterization; Bicinchoninate; Branch linkages; Chemical characterization; D-glucose; Degree of polymerization; Dextransucrase; Endo-dextranase; Leuconostoc mesenteroides; Low degree; Main chains; Number-average; Total carbohydrates; Bacilli; Carbohydrates; Characterization; Fourier transform infrared spectroscopy; Glucose; Nuclear magnetic resonance spectroscopy; Phenols; Sulfuric acid; Thin layer chromatography